Eco-map of an urban area as an essential spatial planning element - V. V. Rukavitsyn; V. N. Exaryan (Известия высших учебных заведений: Геология и разведка)
Background. The article substantiates the creation of “eco-maps” of urban areas as a new environmental assessment tool in strategic planning of cities and urban agglomerations. It is assumed that the eco-map of an urban area should serve as a comprehensive ecological map with the possibility of its further development into a dynamic environmental model.Aim. Development of principles for the creation of eco-maps of urban areas.Materials and methods. Following an analysis of existing methods for the creation of integrated environmental maps, the basic principles for the development of eco-maps of urban areas are proposed. The importance of their implementation is justified.Results. The development of eco-maps of urban areas should rely on the following basic principles: (1) various components of the environment should be taken into account, including differences in the mechanisms and rates of changes in their state; (2) the state of urban ecosystems depends not only on the degree of urban load, but also on the vulnerability of the An eco-map is developed based on an integrated ecological indicator of the urban area.Discussion. The eco-map of a city is a convenient tool for a comprehensive assessment of its ecological state. This tool can be integrated into the existing environmental monitoring system to facilitate reliable forecasting and decision-making processes regarding the development of sustainable urban areas and their adaptation to climate change. This allows for more efficient spatial planning and environmental protection measures aimed at reducing pollution and promoting an ecological culture, which is necessary for the transition to sustainable development.Conclusion. The existing methods for monitoring the state of urban areas provide either a static picture or display individual ecological parameters, without taking into account the links between them. For comparison, the creation of an eco-map assumes the development of an integrated indicator of the ecological state of urban areas, offering the possibility of combining the developed model with data from comprehensive environmental monitoring. The possibility of creating such eco-maps is justified by the availability of modern technologies for collecting and processing large amounts of data. Thanks to advances in sensor technology, monitoring systems, remote sensing and data processing methods, information about the ecological state of an urban area can be collected in real time. This offers opportunities for obtaining a more comprehensive picture of the state of the environment, based on satellite and ground data.